Thermal Modelling and Analysis of Carbide Tool using Finite Element Method - Gupta, Amit (My University, 2007)
The problem of tool wear monitoring in machining operations, has been an active area of research for quite a long time. The accurate prediction of tool wear is important to have a better product quality and dimensional accuracy. In cutting tools the area close to the tool tip is the most important region and conditions at the tool tip must be carefully examined, if improvements in tool performance are to be achieved The present work involves the study of tool wear caused by the change in hardness of single point cutting tool for a turning operation to predict the tool life in orthogonal cutting based on the heat transfer analysis using Finite Element Method (FEM). The Experiments were performed with EN-24 steel as workpiece and Carbide uncoated tool bit as a tool material and the flank wear has been measured experimentally. An empirical relation is used to determine temperature at tool-tip and further Finite Element Method is used to determine the distribution of temperature over the surface of tool and its impact on hardness which is related by an empirical relations. The study shows the effect of Modified temperature due to strain rate on carbide tool to describe the thermal softening of tool material and becomes prone to wear. The results reveal that by increasing process variables in machining the wear and temperature increases causing thermal softening of tool causing it to wear. The results obtained have been verified with the available results from literature for the variation of wear with the temperature and thermal softening of carbide tool. The results prescribed demonstrate the significance of cutting parameters (speed, feed and depth of cut) in thermal analysis for study of the cutting tool wear.
Keywords: Modelling and Analysis of Carbide Tool; Fem; Tthermal Analysis; Heat Effect on Carbide